2018
DOI: 10.1177/1368430218796277
|View full text |Cite
|
Sign up to set email alerts
|

The principle of discrimination: Investigating perceptions of soldiers

Abstract: The principle of discrimination states that soldiers are legitimate targets of violence in war, whereas civilians are not. Is this prescriptive rule reflected in the descriptive judgments of laypeople? In two studies ( Ns = 300, 229), U.S. Mechanical Turk workers were asked to evaluate the character traits of either a soldier or a civilian. Participants also made moral judgments about scenarios in which the target individual (soldier or civilian) killed or was killed by the enemy in war. Soldiers were consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…Overall, participants were more reluctant to order the attack when the targeted individuals were civilians, rather than soldiers. Watkins and Laham (2018) similarly found that U.S. participants made harsher moral judgments of a hypothetical soldier (from a fictional country) who killed an enemy civilian, compared to if he killed an enemy soldier. The findings of this latter study speak directly to the philosophical and legal principle of discrimination, as participants were positioned as uninvolved "third-party" observers to the conflict.…”
Section: The Principle Of Discriminationmentioning
confidence: 88%
“…Overall, participants were more reluctant to order the attack when the targeted individuals were civilians, rather than soldiers. Watkins and Laham (2018) similarly found that U.S. participants made harsher moral judgments of a hypothetical soldier (from a fictional country) who killed an enemy civilian, compared to if he killed an enemy soldier. The findings of this latter study speak directly to the philosophical and legal principle of discrimination, as participants were positioned as uninvolved "third-party" observers to the conflict.…”
Section: The Principle Of Discriminationmentioning
confidence: 88%
“…During the war, in one battle, soldiers from each country fight and kill each other. This background information was based on scenarios developed by Benbaji et al (2015) and Watkins and Laham (2018b). To heighten the chance that participants would read the scenario properly, a timer ensured that participants spent at least 10 seconds on this page.…”
Section: Methodsmentioning
confidence: 99%
“…The character judgments we elicited in previous studies were divided into two sorts, reflecting a previous distinction made in the literature between core goodness traits (e.g., kindness, honesty, compassion, trustworthiness) and value commitment traits (e.g., dedicated, committed, courageous; see Piazza, Goodwin, Rozin, & Royzman, 2014). 11 We expected that if any differences between soldiers on the just and unjust sides were to be found, they would be revealed on judgments of core goodness traits rather than value commitment traitsthere is no reason to expect soldiers fighting for the unjust side to be less courageous or dedicated, but there is perhaps reason to see them as less good overall (though see Watkins & Laham, 2018b). 11 The exact traits rated by participants varied across the previous studies: In Studies 1 and 2, participants rated the target soldiers on 10 traits.…”
Section: Study 5a: Summary Of Prior Studiesmentioning
confidence: 99%
“…This background information was based on scenarios developed by Benbaji et al (2015) and Watkins and Laham (2018b). To heighten the chance that participants would read the scenario properly, a timer ensured that participants spent at least 10 seconds on this page.…”
Section: Methodsmentioning
confidence: 99%
“…The character judgments we elicited in previous studies were divided into two sorts, reflecting a previous distinction made in the literature between core goodness traits (e.g., kindness, honesty, compassion, trustworthiness) and value commitment traits (e.g., dedicated, committed, courageous; see Piazza, Goodwin, Rozin, & Royzman, 2014). 11 We expected that if any differences between soldiers on the just and unjust sides were to be found, they would be revealed on judgments of core goodness traits rather than value commitment traitsthere is no reason to expect soldiers fighting for the unjust side to be less courageous or dedicated, but there is perhaps reason to see them as less good overall (though see Watkins & Laham, 2018b).…”
Section: Study 5a: Summary Of Prior Studiesmentioning
confidence: 99%